2013
DOI: 10.1016/j.biocon.2013.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Developing priorities for metapopulation conservation at the landscape scale: Wolverines in the Western United States

Abstract: a b s t r a c tWildlife populations are often influenced by multiple political jurisdictions. This is particularly true for wide-ranging, low-density carnivores whose populations have often contracted and remain threatened, heightening the need for geographically coordinated priorities at the landscape scale. Yet even as modern policies facilitate species recoveries, gaps in knowledge of historical distributions, population capacities, and potential for genetic exchange inhibit development of population-level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 65 publications
0
47
1
Order By: Relevance
“…, Inman et al. ), identifying characteristics that predict the distribution or presence of wolverines. These efforts have indicated that wolverine are found at higher elevations (Copeland et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…, Inman et al. ), identifying characteristics that predict the distribution or presence of wolverines. These efforts have indicated that wolverine are found at higher elevations (Copeland et al.…”
Section: Discussionmentioning
confidence: 99%
“…, Inman et al. ), and in alpine and subalpine habitats (Aubry et al. ) with higher topographic ruggedness (Krebs et al.…”
Section: Discussionmentioning
confidence: 99%
“…We suggest that the ultimate driver of the observed breeding dispersal is high competition for territories, translated through social interactions between competitors (aggressive forcing) and mother-offspring (territory bequeathal). This demonstration of the complexity in carnivore spatial behaviour provides a stronger foundation for science-based management of wolverine populations that are subject to strong conservation and management concerns in many parts of its distribution (Saether et al 2005;Persson et al 2009;Inman et al 2013). Our results have implications for the design and interpretation of population monitoring schemes (Ellis et al 2014;, harvest strategies (Saether et al 2005) and conflict mitigation .…”
Section: Discussionmentioning
confidence: 99%
“…Sink populations may require conservation interventions to insure that mortality and emigration are at least balanced by reproduction and immigration. Such interventions are common, especially for species in anthropogenically-altered habitats or subject to overexploitation (e.g., Guimaraes et al, 2014;Inman et al, 2013;Wellicome et al, 2013;Wiens et al, 2014). The goals of these interventions usually are to improve local survival and reproduction, with expected response time to be nearly immediate.…”
Section: Introductionmentioning
confidence: 98%